Persistent Symptoms and Association With Inflammatory Cytokine Signatures in Recovered Coronavirus Disease 2019 Patients. (2nd April 2021) - Ong, Sean Wei Xiang; Fong, Siew-Wai; Young, Barnaby Edward; Chan, Yi-Hao; Lee, Bernett; Amrun, Siti Naqiah; Chee, Rhonda Sin-Ling; Yeo, Nicholas Kim-Wah; Tambyah, Paul; Pada, Surinder; Tan, Seow Yen; Ding, Ying; et al.
Abstract: Background: The complications and sequelae of coronavirus disease 2019 (COVID-19) and their effect on long-term health are unclear, and the trajectory of associated immune dysregulation is poorly understood. Methods: We conducted a prospective longitudinal multicenter cohort study at 4 public hospitals in Singapore. Patients with COVID-19 were monitored for a median of 6 months after recovery from acute infection. Clinical symptoms and radiologic data were collected, along with plasma samples for quantification of immune mediators. The relationship between clinical symptoms and immune cytokine profiles was investigated. Results: Two hundred eighty-eight participants were recruited, and follow-up data were available for 183, 175, and 120 participants at days 30, 90, and 180 postsymptom onset, respectively. Symptoms related to COVID-19 were present in 31 (16.9%), 13 (7.4%), and 14 (11.7%) at days 30, 90, and 180. In a multivariable model, age >65 years, non-Chinese ethnicity, and the severity of acute infection were associated with increased likelihood of persistent symptoms. Recovered COVID-19 patients had elevated levels of proinflammatory interleukin (IL)-17A, stem cell factor, IL-12p70, and IL-1β and pro-angiogenic macrophage inflammatory protein 1β, brain-derived neurotrophic factor, and vascular endothelial growth factor at day 180 compared with healthy controls. Higher levels of monocyte chemoattractant protein-1 and platelet-derived growth factor-BB were detected in patients with persistent symptoms, versus symptom-free patients. Conclusions: Approximately 10% of recovered patients had persistent symptoms 6 months after initial infection. Immune cytokine signatures of the recovered patients reflected ongoing chronic inflammation and angiogenesis. Patients with COVID-19 should be monitored closely for emerging long-term health consequences. Abstract : In this cohort study of 183 recovered COVID-19 patients, approximately 10% had persistent symptoms up to 6 months postinfection, associated with elevated MCP-1 and PDGF-BB. Independent of symptoms, recovered patients had cytokine profiles suggestive of ongoing chronic inflammation and angiogenesis.